2022
DOI: 10.3390/ani12141760
|View full text |Cite
|
Sign up to set email alerts
|

Selected Techniques for Physiotherapy in Dogs

Abstract: Physiotherapy is a new dynamically developing field of science in which the original idea was to improve the care for convalescent patients. Its positive effects observed in humans suggested the need for the adaptation and implementation of human physiotherapy techniques in animal care. Dogs are the second group of animals that undergo physiotherapy most frequently. These animals are diagnosed with a number of locomotor system problems, which may be congenital and are often related to the breed or acquired. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
3
1
Order By: Relevance
“…Despite their differing mechanisms of action, no differences were observed between ES and LASER therapy. Interestingly, neither ES nor LASER therapy resulted in greater recovery after MPL surgery, which was contrary to our expectations, as we believed that the analgesic effects of these approaches would promote a more rapid post-operative recovery [12]. Previous studies revealed that ES pain control mechanisms involve stimulating signals from A-β fibers to activate inhibitory neurons in the substantia gelatinosa of the dorsal horn of the spinal cord [15][16][17].…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…Despite their differing mechanisms of action, no differences were observed between ES and LASER therapy. Interestingly, neither ES nor LASER therapy resulted in greater recovery after MPL surgery, which was contrary to our expectations, as we believed that the analgesic effects of these approaches would promote a more rapid post-operative recovery [12]. Previous studies revealed that ES pain control mechanisms involve stimulating signals from A-β fibers to activate inhibitory neurons in the substantia gelatinosa of the dorsal horn of the spinal cord [15][16][17].…”
Section: Discussioncontrasting
confidence: 86%
“…This study focuses on both primary rehabilitation management and post-operative rehabilitation approaches [9,14,23,24]. In primary management, the emphasis of rehabilitation is on enhancing the animal's physical functionality and alleviating any associated pain [12]. This role becomes particularly important in situations where surgical interventions may not be the most suitable option, often due to the animal's specific condition or the owner's preferences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, IRT has been suggested as a tool that can help to recognize injuries and changes in surface temperature and be implemented in the recovery process, particularly in cases requiring physical therapy [ 18 , 19 , 20 , 21 ]. Therapies such as acupuncture, photo biomodulation, electrostimulation, or thermotherapy can modify the superficial thermal response associated with the inflammatory process and pain [ 22 , 23 , 24 ]. Some studies have shown that, for example, electrostimulation with transcutaneous electrical nerve stimulation (TENS) prevents tissular necrosis [ 25 ], while high-intensity laser therapy applied to racehorses with back pain has been shown to decrease the palpation score for pain [ 26 ].…”
Section: Introductionmentioning
confidence: 99%